Review of bridge vibration and future direction - Akib, S.; Fayyadh, M.M.; Razak, H.A. (2010)
The objective of this review paper is to sum up all the topics related to conventional and integral bridge vibration and focus the effects of scour on conventional and integral bridge and finally to suggest future directions of research and innovation. Research on separate issues on bridge vibration, integral bridge vibration, scour on bridge and scour on integral bridge are well emphasized. Issues of local scour on vibration still not been explored in the research. The future direction and innovation are highlighted in the future research on conventional and integral bridge vibration related to localized scour to fill the gap of the research.